Flavonoid Effects of Water Extraction on Total Flavonoid Content and Biological Activities between Natural and Cultured Wolffia globosa (Roxb.) Hartog & Plas - Rucksakaew, Kanyarat; Damsud, Thanakorn; Chankaew, Wanninee (Princess of Naradhiwas University Journal, 2019)
The aim of this study was to compare the total flavonoid content and biological activities between natural and cultured Wolffia globosa. Natural W. globosa was collected from Khao Chai Son district,Phatthalung province (8o9’41”N, 99o43’31”E). Cultured W. globosa was culturedin a laboratory by chicken manureas.Total flavonoid content (TFC) was analyzed by aluminum chloride colorimetric assay method. Additionally, biologicalactivitiesweremeasuredbyDPPH,ABTSradicalscavengingassay,andalphaglucosidase inhibition, determined from the extracted with different conditions, it is to say at 4 ºC/24 h, 24 ºC/12 h, 50 ºC/6 h, 75 ºC/3 h and 100 ºC/1.5 h. The results found that the TFC and thebiological activities weresignificantly different between extraction method (p<0.05). The highest of TFC found was in 100 ºC/1.5 h (27.249±0.10 mg QE/g extract). The highest activity of scavenging DPPH and ABTS radical were found in W. globosa from natural (75 ºC/3 h method) with IC 50= 0.017±0.00 and 0.016±0.00 mg/ml, respectively. The highest inhibition of maltase and sucrase activities was found in 100 ºC/1.5 h and 4 ºC/24 h method of W. globosa from natural with IC50= 8.346±0.03 and 1.723±0.02 mg/ml, respectively. Inaddition, according to Peason’s correlation coefficient between all extract with IC50 of all biological activities, TFC were contribution major in its alpha glucosidase inhibition. This results obtained in this study clearly indicate that W. globosa has a significant potential to be used as natural antioxidants and, consequently, to be developed as health product.